Variation in Epifloral Community Composition according to heavy metals in sediment of Tapi, Surat, India - Patel, Khushboo; Manoj, Kapila (International Journal of Scientific Research in Biological Sciences, 2020)
Epifloral communities play a significant role in monitoring the environmental pollution. The study was undertaken to understand the epifloral community composition in relation to heavy metals (Cu, Zn, Ni, Pb, Cd) in sediment at different sites of Tapi River. During the study total 23 species of 3 group of epifloral community were identified Bacillariophyceae, Chlorophyceae and Cyanophyceae. Among these groups Chlorophyceae were most abundant in both season and cyanophyceae were reported least dominant at all the sites. Number of species of Bacillariophyceae was reported higher during wet season at all sampling sites. According to heavy metal concentration epifloral community composition was also changed.